Appropriate Information Technology for E-Government Service of Cooperatives in Sampit City Web-Based - Wira Pradana; Nurahman Nurahman (STMIK Budi Darma, 2021)
This research is motivated by the application of information systems through e-Government which is the main problem in the development of information systems applied to the Sampit City Cooperative Service, to develop information and sites that already exist and can be used properly and are beneficial for MSMEs in using cooperative services. The type of research used in this study is data sharing, the method used is the method of data collection and system development. The research result obtained is information system which is applied to the Department of Cooperatives through the creation of a website can help p roses collection more effective and efficient related registration of members , p romosi product data and product advancements SMEs as well as web site also helps better services to SMEs and the public thereby improving the relationship between the two parties and illustrates the implementation of a good information system from the public authorities to the local area